MDMX acts as a pervasive preleukemic-to-acute myeloid leukemia transition mechanism - Ueda, K; Kumari, R; Schwenger, E; Wheat, JC; Bohorquez, O; Narayanagari, S-R; Taylor, SJ; Carvajal, LA; Pradhan, K; Bartholdy, B; Todorova, TI; Goto, H; et al. (Cell Press, 2021)
MDMX is overexpressed in the vast majority of patients with acute myeloid leukemia (AML). We report that MDMX overexpression increases preleukemic stem cell (pre-LSC) number and competitive advantage. Utilizing five newly generated murine models, we found that MDMX overexpression triggers progression of multiple chronic/asymptomatic preleukemic conditions to overt AML. Transcriptomic and proteomic studies revealed that MDMX overexpression exerts this function, unexpectedly, through activation of Wnt/β-Catenin signaling in pre-LSCs. Mechanistically, MDMX binds CK1α and leads to accumulation of β-Catenin in a p53-independent manner. Wnt/β-Catenin inhibitors reverse MDMX-induced pre-LSC properties, and synergize with MDMX-p53 inhibitors. Wnt/β-Catenin signaling correlates with MDMX expression in patients with preleukemic myelodysplastic syndromes and is associated with increased risk of progression to AML. Our work identifies MDMX overexpression as a pervasive preleukemic-to-AML transition mechanism in different genetically driven disease subtypes, and reveals Wnt/β-Catenin as a non-canonical MDMX-driven pathway with therapeutic potential for progression prevention and cancer interception.